The Psychological Aspect of Woman as Reflected in “Wrecking Ball” Music Video - Regina, Mica (LANTERN (Journal on English Language, Culture and Literature), 2014)
“Wrecking Ball” is a song that sung by American singer, Miley Cyrus. The lyric tells about a woman who feel so sad, depressed and frustrated. Wrecking ball symbolizes the phallic symbolism. The purpose of the study is to know the content of music video and to analyze the elements of poetry inside the lyric of Wrecking Ball. The study used intrinsic and extrinsic theories and library research method to compile the data. Library research is used to get literary and psychological theories. The finding of the study is the connotation of Love, Sex, and Pscyhosexual Stage inside of Wrecking Ball.